Talinum paniculatum (Jacq.) Gertn (Kajian Pemanfaatannya sebagai Bahan Pangan dan Bioaktivitasnya - Marina Silalahi (Jurnal Pro-Life, 2022)
Talinum paniculatum (Talinaceae), known by local Indonesians as Javanese ginseng, has long been used as a vegetable and traditional medicine, but information is limited to certain circles. This study aims to explain the benefits of T. paniculatum as a food ingredient and its bioactivity. This research is library research obtained from Google Scholar using the keywords T. paniculatum, uses T. paniculatum and T. paniculatum bioactivity. In Indonesia, T. paniculatum is easily found in the surrounding environment, either intentionally planted or growing wild and has been traded in traditional markets as a vegetable ingredient. The use of T. paniculatum as a food ingredient is related to its nutritional content in the form of protein, fiber, ascorbic acid, magnesium, potassium, and calcium. The bioactivity of T. paniculatum includes: increasing sexual activity and estrogenic activity, anti-microbial, aphrodisiac, anti-hypertensive, anti-oxidant and anti-aging. Talinum paniculatum has the potential to be developed as a healthy food ingredient, especially as an anti-microbial and anti-aging.